Pengaruh Penambahan Glutathione (GSH) Terhadap Mikroalga Chlorella sp. Dalam Menyisihkan Logam Ni Limbah Cair Elektroplating Menggunakan Airlift Bioreactor - Karamy, Afrilia Geishy; Elystia, Shinta; Hs, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
An alternative technology for removing Ni metals of electroplating wastewater is biosorption using microalgae Chlorella sp. Chlorella sp. has the ability to respond to the toxic effects of heavy metals by forming phytochelatin. Phytochelatin can be synthesized enzymatically from glutathione (GSH) which response to metal ions. The purpose of this study is to know the effect of the addition of GSH on the process of metal biosorption. The study was conducted with variations in the addition of GSH (0, 5, 10 and 15 mg/L) and variations in contact time (1, 2, 3, and 4 days). Based on the results of the study, The highest removal of Ni metal at 4 days contact time with the addition of GSH 15 mg/L with removal efficiency of 83%. Keyword: Chlorella sp., glutathione (GSH), limbah cair elektroplating, Ni, Phytochelatin